The moral aspect of the effectiveness and the effeciency of the comportment of people in the organization
The economy arranges human activity in the sphere of the farming, it cannot do without notions settled on the basis of human nature and nature of society, because economic activity of a man is not only his attitude towards things, but first of all to other people as individual beings, and to their teams and social groups. Because economic activities belong to a group of human occurrences therefore their understanding requires knowledge of human nature and factors financially elusive belonging to psychology and ethics and having impact on the human behaviour. The research of these occurrences is based on lots of data, by no means statistical. In research of economic phenomena metaphysical notions about human nature are the most important, about its origin, destiny, selfesteem and mutual bound among people. In this way the range of political power cannot be determined by empirical research